17BIPHE2, an engineered cathelicidin antimicrobial peptide with low susceptibility to proteases, is an effective spermicide and microbicide against Neisseria gonorrhoeae. Issue 11 (2nd September 2022) - Lee, Seung Gee; Kiattiburut, Wongsakorn; Khongkha, Thitiporn; Schinkel, Stephanie C Burke; Lunn, Yvonne; Decker, Aaron P; Mohammadi, Avid; Vera-Cruz, Ana; Misra, Avika; Angel, Jonathan B; Anderson, Deborah J; Baker, Mark; et al.
Abstract: STUDY QUESTION: Is 17BIPHE2, an engineered cathelicidin antimicrobial peptide with low susceptibility to proteases, a better spermicide in cervicovaginal fluid (CVF) than its parental peptides, LL-37 and GF-17? SUMMARY ANSWER: At the same mass concentration, 17BIPHE2 exhibited the highest spermicidal activity on human sperm resuspended in CVF-containing medium. WHAT IS KNOWN ALREADY: LL-37 and its truncated peptide GF-17 exert both spermicidal and microbicidal activities, although they are prone to proteolytic degradation in body fluids. STUDY DESIGN, SIZE, DURATION: Spermicidal activities of 17BIPHE2 were evaluated in vitro in mouse and human sperm, both resuspended in medium, and then on human sperm incubated in CVF-containing medium; in the latter condition, the spermicidal activity and peptide stability in CVF of 17BIPHE2 were compared with that of LL-37 and GF-17. The in vivo contraceptive effects of 17BIPHE2 and the reversibility thereof were then assessed in mice. Finally, in vitro microbicidal effects of 17BIPHE2 on Neisseria gonorrhoeae were determined. PARTICIPANTS/MATERIALS, SETTING, METHODS: Sperm motility and plasma membrane integrity were assessed by videomicroscopy and exclusion of Sytox Green, a membrane-impermeable fluorescent dye, respectively. Successful in vitro fertilization (IVF) was determined by the presence of two pronuclei in oocytes following their coincubation with capacitated untreated or 17BIPHE2-treated sperm. Sperm alone or with 17BIPHE2 were transcervically injected into female mice and successful in vivo fertilization was indicated by the formation of two-cell embryos 42-h postinjection, and by pregnancy through pup delivery 21–25 days afterwards. Peptide intactness was assessed by immunoblotting and HPLC. Reversibility of the contraceptive effects of 17BIPHE2 was evaluated by resumption of pregnancy of the female mice, pretranscervically injected with 17BIPHE2, following natural mating with fertile males. Minimum inhibitory/bactericidal concentrations of 17BIPHE2 on N. gonorrhoeae were obtained through microdilution broth assay. MAIN RESULTS AND THE ROLE OF CHANCE: At the same mass concentration, 17BIPHE2 was a more effective spermicide than LL-37 or GF-17 on human sperm resuspended in CVF-containing medium, with the spermicidal concentration of 32.4 µM. This was mainly due to lower susceptibility of 17BIPHE2 to CVF proteases. Importantly, the reproductive tract of mouse females treated three times with 32.4 µM 17BIPHE2 remained normal and their fecundity resumed after stopping 17BIPHE2 treatment. LIMITATIONS, REASONS FOR CAUTION: For ethical reasons, the inhibitory effects of 17BIPHE2 on fertilization and pregnancy cannot presently be performed in women. Also, while our study has proven the effectiveness of 17BIPHE2 as a spermicide for mouse and human sperm in vitro, dosage formulation (e.g. in hydrogel) of 17BIPHE2 still needs to be developed to allow 17BIPHE2 to remain in the vagina/uterine cavity with controlled release for its spermicidal action. WIDER IMPLICATIONS OF THE FINDINGS: Since 17BIPHE2 also exerted bactericidal activity against N. gonorrhoeae at its spermicidal concentration, it is a promising candidate to be developed into a vaginal multipurpose prevention technology agent, thus empowering women against unplanned pregnancies and sexually transmitted infections. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the Canadian Institutes of Health Research (PJT 173268 to N.T.). There are no competing interests to declare. TRIAL REGISTRATION NUMBER: N/A.